Dr. Tahir Taunsvi as a Researcher of Dr. Saleem Akhtar - Abbas, Qamar; karim, Naila Abdul; Perveen, Fauzia (sourcecoder, 2023)
Dr. Tahir Taunsvi (1948-2019) is a well-known researcher, critic, poet, educational expert and successful administrator. His literary services spreads over half of the century .His more than seventy seven publications (books), three hundred articles have become a precious asset of Urdu language and literature. His main domain is Urdu research. His research work on Urdu poetry, prose and linguistics has much importance. He took great interest towards Iqbal studies, Ghalib studies and mysticism by making them the themes of his research work. A multidimensional and valuable asset of his autobiographical research, textual research and compilations of literary essays on variety of literary topics have made his research work more valuable for students and research scholars .Literary personalities(prominent and common) are his big and important topic of research. He wrote about almost more than two hundred literary personalities. He published forty one books about these personalities and introduced their life history, their publications, their themes, their styles and worth of their important work .In this article, the author has brought to light and analyzed the Dr.Tahir Taunsvi’s research work about renowned Urdu researcher, critic and short story writer Dr.Saleem Akhtar.